The position of the Kingdom of Saudi Arabia on the Palestinian issue during the years (1927-1931) - Mahmoud, Jameel Abd; Rahe, Ibtisam Hamoud Muhammad (Journal of Ecohumanism, 2025)
The Palestinian cause is one of the most prominent Arab and Islamic issues that has received the attention of the Kingdom of Saudi Arabia since its establishment. The Kingdom realized early on the importance of supporting the Palestinian people in their journey towards regaining their legitimate rights and establishing their independent state on their land. Based on its Islamic and Arab principles, the Kingdom made the Palestinian cause a fundamental focus of its foreign policies, as it stood by the Palestinian people in various international forums and provided political, economic and humanitarian support. In this research, we will review the Kingdom’s position on the Palestinian issue, starting with diplomatic efforts, through the initiatives it has presented to achieve peace, and ending with the ongoing support it provides at the regional and international levels. We will also discuss the impact of this position in strengthening Arab and Islamic solidarity towards the Palestinian issue.